2018
DOI: 10.1016/j.bja.2017.11.080
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative fasting in children: review of existing guidelines and recent developments

Abstract: The current guidelines for preoperative fasting recommend intervals of 6, 4, and 2 h (6-4-2) of fasting for solids, breast milk, and clear fluids, respectively. The objective is to minimize the risk of pulmonary aspiration of gastric contents, but also to prevent unnecessarily long fasting intervals. Pulmonary aspiration is rare and associated with nearly no mortality in paediatric anaesthesia. The incidence may have decreased during the last decades, judging from several audits published recently. However, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 40 publications
3
75
0
10
Order By: Relevance
“…We also observed that fasting time was longer than the recommended guidelines of 2 hours in a large proportion of our patients (median 6.4 hours, IQR: 4.4–12.6 hours, Table ). These findings are consistent with previous reports that despite recommendations for clear liquid fasting time of 2 hours, children actually have longer fasting times . The European Society for Paediatric Anaesthesiology recently published a consensus statement advocating for clear liquid fasting time of 1 hour prior to elective general anesthesia…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We also observed that fasting time was longer than the recommended guidelines of 2 hours in a large proportion of our patients (median 6.4 hours, IQR: 4.4–12.6 hours, Table ). These findings are consistent with previous reports that despite recommendations for clear liquid fasting time of 2 hours, children actually have longer fasting times . The European Society for Paediatric Anaesthesiology recently published a consensus statement advocating for clear liquid fasting time of 1 hour prior to elective general anesthesia…”
Section: Discussionsupporting
confidence: 91%
“…findings are consistent with previous reports that despite recommendations for clear liquid fasting time of 2 hours, children actually have longer fasting times 3,18. The European Society for PaediatricAnaesthesiology recently published a consensus statement advocating for clear liquid fasting time of 1 hour prior to elective general anesthesia.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, fasting periods of 6 or more hours did not ensure an empty stomach. As summarized in Table , the majority of our patients had recently eaten fried/fatty food or meat, and the majority reported severe pain and received opioid analgesia, all of which can slow gastric emptying . Our findings mirror those of Bouvet and colleagues, who demonstrated that 56% of adults undergoing emergency surgical procedures had a full stomach at the time of anesthesia despite a mean fasting duration of 18 hours.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike patients fasting prior to elective sedation, PED patients awaiting procedural sedation often have painful injuries, are frequently treated with opioids, and may have eaten large fatty meals immediately preceding injury, all of which can slow gastric emptying . Large, multicenter studies are necessary to estimate the risk of pulmonary aspiration in any setting .…”
mentioning
confidence: 99%